The role of maternal milk in endocrine regulation of sucklings - Štrbák, Vladimír, 1943- (Bratislava : Veda, 1985)
Resumé rus.
Keywords: mlieko materské -- fyziológia -- sekrécia; systém endokrinný; novorodenec; laktácia; dojčenie